Floral Traits Predict Frequency of Defecation on Flowers by Foraging Bumble Bees. Issue 5 (18th September 2019) - Bodden, Jonah M; Hazlehurst, Jenny A; Wilson Rankin, Erin E
Abstract: Flowers may become inoculated with pathogens that can infect bees and other critical pollinators, but the mechanisms of inoculation remain unclear. During foraging, bees may regurgitate or defecate directly onto flower parts, which could inoculate flowers with pollinator pathogens and lead to subsequent disease transmission to floral visitors. We tested if captive eastern bumble bees ( Bombus impatiens ) (Cresson) (Hymenoptera: Apidae) defecate on floral surfaces during foraging and if flower shape played a role in the probability of defecation and the quantity of feces deposited on floral surfaces. Captive Bombus impatiens were fed a solution of fluorescent dye and sucrose, then allowed to forage freely on flowers of a variety of shapes in a flight cage. Flowers were then examined under ultraviolet light for fluorescing fecal matter. We found that bumble bees did defecate on floral surfaces during foraging and that composite flowers with a large area of disk flowers were the most likely to have feces on them. Our results point to defecation by bumble bees during foraging as a potential mechanism for inoculation of flowers with pollinator pathogens and suggest that flower shape could play a significant role in inoculation.